2009
DOI: 10.1007/s11128-009-0102-4
|View full text |Cite
|
Sign up to set email alerts
|

Interband transitions and interference effects in superconducting qubits

Abstract: We investigate phase-sensitive interference effects in a periodically sin(2π f rf t)-driven, artificial two-state system connected to a microwave resonator at f LC 800 MHz. We observe two kinds of multiphoton transitions in the twostate system, accompanied by: (1) Several quanta from the drive at f rf and (2) one quantum at f rf and several at f LC . The former are described using phase-sensitive Landau-Zener transitions, while the latter are discussed in terms of vibronic transitions in diatomic molecules. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The charge can then be related to the charge-qubit occupation, the derivative of which (under resonant driving) exhibits sign changes. Similar sign-changing response under strong driving was recently studied for qubits probed by an LC (tank) circuit for capacitive coupling 14,15 as well as for inductive coupling 16,17 . Thus, in the first part of this work (Section II) we study the situation where the strong-driving qubit's state is probed by the NR.…”
supporting
confidence: 57%
“…The charge can then be related to the charge-qubit occupation, the derivative of which (under resonant driving) exhibits sign changes. Similar sign-changing response under strong driving was recently studied for qubits probed by an LC (tank) circuit for capacitive coupling 14,15 as well as for inductive coupling 16,17 . Thus, in the first part of this work (Section II) we study the situation where the strong-driving qubit's state is probed by the NR.…”
supporting
confidence: 57%
“…Alternatively, the qubit was probed via an inductive coupling to the resonant circuit (Tuorila et al, 2013). Two types of multi-photon transitions in this system were further studied by (Paila et al, 2009). A similar aluminum Cooper pair box was probed via the reflection coefficient in a coupled electric resonator in Refs.…”
Section: A Superconducting Circuitsmentioning
confidence: 99%
“…Such transitions were studied both in microscopic systems [2,125], and in the Josephson-junction qubits [126][127][128]. Also for the case of a flux qubit it was demonstrated that the persistence of Rabi oscillations can be supported by either the low-frequency signal [129] or induced by noise [130].…”
Section: Dynamical Behavior Of a Two-level Systemmentioning
confidence: 99%